Avaliação do desgaste de uma ponta abrasiva diamantada na retificação do metal duro - Fernandes, Lara Souza Martins (Universidade Federal de São Carlos, 2024)
Grinding is a machining process that uses wheels with high-hardness abrasive grains to remove material. It is employed in manufacturing components requiring high-quality surfaces and dimensional accuracy. Grinding with a point grinding wheel is a variant within the various possible operations, in which small, single-layer superabrasive tools are applied for the precise machining of complex three-dimensional surfaces. Despite its flexibility, the process faces several challenges. Reducing the tool diameter can cause increased vibration, excessive tool wear, form and dimensional deviations and damages to the surface. Therefore, different ways of process optimization have been investigated, but the literature on grinding with point grinding wheels is limited, focusing mainly on its application to nickel and titanium alloys. Based on the above, this study aimed to characterize the wear of the point grinding wheel and determine the behavior of surface roughness during grinding of WC-5%Co alloy. For this purpose, two cutting speeds were tested and a wear-determination method based on the Abbott-Firestone curve was used. A higher cutting speed increases the material removal volume until tool life end, leading to a lower tool wear rate. The workpiece roughness decreased with the increase in the material removal volume, and greater initial grain protrusions caused higher values of surface roughness.
Assessment of the wear of a diamond abrasive tip in grinding of cemented tungsten carbide
Keywords: Retificação; Ponta abrasiva; Metal duro; Desgaste; Grinding; Point grinding wheel; Cemented carbide; Wear; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO